Death Anxiety Perawat Pada Masa Covid 19: Systematic Literature Review - Pragholapati, Andria; Haryati, Iis (Jurnal Keperawatan Komplementer Holistic, 2023)
Hundreds of thousands of people have been infected by this virus, this virus is called the 2019 Coronavirus Disease or Covid-19. Nurses as health workers who have the most contact with patients have a risk of contracting the Covid-19 virus, this is due to the emergence of worry, fear, panic and helplessness so that they can experience death anxiety. The purpose of this study was to determine the description of nurses' death anxiety during the Covid-19 period. Methods: This study is a systematic review by searching for articles using the Pubmed, Google Scholar and Science Direct databases to find articles according to the inclusion and exclusion criteria. Keywords used by Nurses, Death Anxiety, Covid-19; nurse, death anxiety, Covid-19. Results: Based on the results of the study, there were 7 articles that discussed nurses' death anxiety when providing care to Covid-19 patients. Conclusion: Nurses caring for COVID-19 patients are at high risk of experiencing death anxiety. Death Anxiety can be prevented or reduced by using possible solutions and effective interventions such as online psychological counseling services, CBT therapy, and multidisciplinary mental health teams to support and facilitate appropriate coping mechanisms for frontline nurses caring for COVID-19 patients.